Building Information Modeling: digital technology serving architectural design - Garagnani, Simone; Cinti Luciani, Stefano; Mingucci, Roberto (DISEGNARECON, 2011)
The architectural design is a complex set of transactions where the knowledge proper of many disciplines meets the professionalism of many people involved as well, still mainly interacting via paper-based communications. Building Information Modeling, whom state of the art is the subject of this paper, is first of all a design strategy which aspires to be much more than a mere information exchange tool: it is rather a coordinated and holistic approach aimed to assist engineers, designers, developers, decision makers, contractors and owners. A digital model derived from B.I.M. software allows, among other things, to integrate the necessary data to all the actors, keeping it up to date, facilitating in real time the changes of the building components and describing the project in a coherent way.